GEOINFORMATION SUBSYSTEM OF THE ARMED FORCES OF UKRAINE AUTOMATED COMMAND AND CONTROL SYSTEM AS A TOOL OF THE MILITARY PURPOSE INFORMATION AND ANALYTICAL SYSTEMS INTEROPERABILITY - Fedchenko, O.; Lytvynenko, N.; Lavrinchuk, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
To solve the multi-vector tasks of military management it is necessary to use technologies that effectively combine space and time with significant accompanying data in the form of attributive information about operational facilities, background information about the theater (area) of hostilities, climatic conditions, intelligence and etc. It is for this purpose that the armies of many countries around the world use geographic information technology. To date, the Armed Forces of Ukraine have implemented a number of information and analytical systems that solve the problems of automation of mobilization deployment, defense planning, logistics, personnel, financial support, and all of them should be integrated into the Unified Automated Command and Control System (UACCS). Information in such information-analytical systems is processed at all levels of management according to the rules and algorithms developed in these systems. In the process of planning the use of troops (forces) involved a number of people responsible for certain areas of support. It is clear that the requirements for the submission of information to perform the tasks of a particular activity are different. In this situation, geographic information support is required to be able to create the necessary information environment for each individual official, without losing the properties of the management system for consistency and synchronization of all its elements. The implementation of this requirement is achieved by using a single core of geographic information software, which provides software developers and users with basic geographic information services and tools for their joint use in performing specialized tasks. In this case, the specified core should operate in a spatially distributed environment, be protected from external interference and be as accessible as possible to internal users in accordance with the established distribution of powers. The article considers the geo-information subsystem of the UACCS of the Armed Forces of Ukraine as a tool to ensure interoperability with existing information and analytical systems in the Armed Forces of Ukraine and new ones planned for deployment, using other hardware and software. The service-oriented architecture of the geoinformation support subsystem of the military management system, which should consist of separate subject-oriented modules within the general system, uses functional components that are built into an open, extensible software and hardware platform to achieve interoperability using spatially distributed information. rules within the framework of basic services that support the exchange of messages, conversion of data for further dissemination (distribution) by publishing and subscribing to standard and specially designed design templates.